Análise geoambiental em unidades de conservação de proteção integral no semiárido sergipano - Souza, Heloísa Thaís Rodrigues de (2016)
Historically, the northeastern forest activity has been characterized by a predatory exploitation model of natural ecorecursos, notably from the caatinga (ecosystem rich in biodiversity), by the disorganization of production and by the low valorization and diversification of the forest products of the semiarid, limited mainly to firewood And coal. Nonetheless, this activity contributes significantly to regional development. In order to protect biodiversity in the semi-arid region of Sergipe, it is necessary to create planning and management mechanisms, with the involvement of the entire society. Among these mechanisms exists as a public policy in situ conservation, in Brazil, one of the main strategies is the creation of Conservation Units (CUs). In this context, the present thesis results in the evaluations of the dynamics of the forest fragments in Conservation Integrated Units in the Semi-Arid Sergipano, promoting concrete recommendations for management purposes and consequently subsidies for effective and / or elaboration of the management plan of the same, Basic assumption of the environmental sustainability of these remnants, verified through environmental indicators (biotic and abiotic). In this sense, the objective of this research was to analyze the effects of the implantations of the Conservation Units of Integral Protection of the State of Sergipe, the conservation of the forest fragments in the Semi - arid, evaluating the socio - environmental aspects of the same through sustainability indicators. Thus, this research made possible the necessary elements to characterize the biotic and abiotic situation of the remaining Caatinga forest remnants in the State, due to the creation of the CUs, looking at the environmental problems resulting from degradation processes and inadequate management that contributed to the current Framework, pointing out possibilities of actions for their better conservation and sustainability. The results of the analysis of the indicators (biotic and abiotic) indicate different levels of anthropization of the caatinga, which result in geoenvironments that have different regeneration capacities, even being within the macro vegetative complex. Thus, monitoring has become important to create subsidies for the management of the caatinga to be carried out according to the fragilities of each micro-environment. In addition, the sustainable forest management of the forest stands out from the use of the phytotherapeutic potential of the vegetal species of the sergipana caatinga.